Energy harvesting frictionless brakes for short-haul aircraft: thermal and electromagnetic feasibility of an axial-flux machine for a landing gear drive system - Deja, Jakub; Akbari, Amir; Dayyani, Iman; Stote, Martin; Lowther, David (American Institute of Aeronautics and Astronautics (AIAA), 2023)
The aviation industry is currently responding to climate change with, among other technologies, electrification of aircraft, and the corresponding onboard electrical architecture provides an opportunity for electromagnetic brakes. The present work introduces a multistage yokeless and segmented armature (YASA) electric machine that replaces friction brakes and harvests kinetic energy throughout a landing. The study establishes the optimal trade-off between weight and electromagnetic torque and translates it into the design requirements for the development of an electric machine. Electromagnetic modeling is conducted using a quasi-3D transient approach and static 3D validation. The results reach 120 Nm/kg active material torque density at approximately 50 A/mm² current density. The proposed solution enables fitting an electric machine that decelerates an aircraft at autobrake level LOW for Airbus and the "1" and "2" settings for Boeing. A thermal analysis follows, where a novel cruise altitude cooling method is proposed.